John Dewey’s Pragmatist Aesthetics: The Specificity and Vitality of Aesthetics - Vaamonde, Marta (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Everyday Aesthetics, radicalizing Dewey’s notion of the continuity between art and experience, aims to find aesthetic qualities in ordinary experience. The problem is that it reduces the aesthetic significance that Dewey attributed to artistic production. Analyzing Dewey’s work and its interpreters, I will demonstrate that the continuity of ordinary experience and art is what lends art its vital and distinctive character. The work of art contributes to developing other ways of seeing and acting in the world, reinforcing life in common, the basis of democracy.